Den tyske hemmelighed - Johansson, Lars (Denmark : Final Cut Productions APS, 2004)
Kirsten Blohm leaves Denmark traveling to the place of her birth – to the place where the American prison in post-war Germany was. As captured by her husband, director Lars Johansson, the story of Kirsten Blohm’s family background turns out to be more fantastic than fiction, involving captivity and flight, secrecy and lies. Blohm, born in 1946, was raised by her grandparents. She did know her mother, the beautiful but cold Signe Gondrup, but Signe never wanted to disclose anything about her life, let alone about her daughter's father. Following her elusive mother's footsteps, Blohm’s journey takes her to the Czech Republic and Germany where she uncovers a series of dramatic events as well as embarrasing skeletons in the closet.
Duration: 01:28:00
Keywords: Documentary films